Sensory profiles, behavioral problems, and auditory findings in children with autism spectrum disorder - GÜNDOĞDU, ÜMMÜGÜLSÜM (My University, 2023)
Objective: This study examined the relationship between sensory processing (SP) differences and behavioral problems in children with autism spectrum disorder (ASD). We also investigated whether audiological test results could objectively detect auditory processing differences. Method: Forty-six children with ASD, ages 3–9 years, were enrolled in the study. Problematic behaviors and sensory processing of children were assessed using scales. The otolaryngologist performed a detailed head and neck examination and a formal audiological examination was performed by an audiologist. Results: Stereotypy, hyperactivity, and irritability were related to sensation seeking. Stereotypy was also associated with visual processing. Touch processing differences was related to irritability and inappropriate speech. Lethargy was associated with auditory processing. There were no differences in SP and behavior problems in the children whose audiological profiles could be measured between those who passed or failed the test. Conclusion: There was an association between SP differences and behavioral problems in children with ASD, supporting previous studies. Audiological test results did not reveal the SP differences documented in the parent forms.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Gelişim Psikolojisi; Sağlık Bilimleri; Social Sciences and Humanities; Psychology; Developmental Psychology; Health Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Psikiyatri; PSİKOLOJİ, GELİŞTİRME; Clinical Medicine (MED); Natural Sciences (SCI); PSYCHIATRY; PSYCHOLOGY; PSYCHOLOGY, DEVELOPMENTAL; Gelişim ve Eğitim Psikolojisi; Sosyal Bilimler ve Beşeri Bilimler; Psikiyatri ve Ruh Sağlığı; Developmental and Educational Psychology; Social Sciences & Humanities; Psychiatry and Mental Health; auditory profiles; autism spectrum disorder; behavioral problems; children; sensory profiles; autism spectrum disorder; sensory profiles; behavioral problems; auditory profiles; children